Spatial and Temporal Variability of Mixed Layer Depth (MLD) in Eastern Indian Ocean (EIO): 1998-2020 - Yuliardi, Amir Yarkhasy; Firdaus, Randi (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract Mixed Layer Depth (MLD) plays an important role in various aspects of oceanography. MLD has a characteristic parameter value that is uniform with depth. MLD has an important role for local, regional, and global phenomena. Indonesia, which is surrounded by the East Indian Ocean, will be directly influenced by the dynamics of MLD. This study aimed to analyze seasonal variability and MLD between years. Mixed layer depth data from the ARMOR3D Dataset Copernicus-Marine Environment Monitoring Service was used for MLD analysis with a threshold of 0.2oC for temperature. Wavelet analysis showed that MLD variability in the eastern Indian Ocean spans from intra-seasonal to interannual scales. Time series analysis showed a complex relationship between MLD and SST in the annual and interannual periods which indicates a different process. The MLD monthly climatology at point 90E, 0 showed the depth of mixed layers is deeper during the east monsoon (JJA-SON) ranging from 50-65 m compared to the west monsoon (DJF-MAM) which has a range of 20-40 m. Spatially the MLD in the south of the equator is deeper than in the north. Interannually, MLD is heavily influenced by the Indian Ocean Dipole. MLD depth is deeper in nIOD with a maximum depth in the range of 100 m compared to pIOD. MLD with maximum depth in the strong nIOD phase is around the equator and the pIOD phase is south of the equator. The study also showed that inter-annual variability in regions around the mainland showed a stronger response. Highlight Researh ARMOR3D data has fairly good accuracy as evidenced by data validation In general, EIO is influenced by intra-seasonal, seasonal and inter-annual variability The shallowing and deepening of the MLD are strongly correlated with the wind speed associated with the annual cycle IOD has a strong role in MLD which looks significantly different, especially when nIOD and pIOD